A study on in-service distance education for secondary school teache rs in Uganda developing a framework for q uality teacher education programmes - Aguti, Jessica Norah (Kampala, 2003)
This study focused on examining distance education In-Service Teache r Education (INSET) programmes for the education of secondary school te achers in Uganda. The study traced the historical development of distan ce education, explored some of the theories underpinning it and related these to distance education in Uganda.
Unpublished thesis (PHD)-University of Pretoria, 2003.
This thesis was supervised by Prof. W.J. Fraser and
Keywords: Distance education -- Uganda; Teachers -- Employees -- Training of; Education, Secondary -- Uganda; CD-Recordable.